Mitochondrial Genome of Brugia malayi Microfilariae Isolated From a Clinical Sample - Qing, Xiong; Kulkeaw, Kasem; Wongkamchai, Sirichit; Tsui, Stephen Kwok-Wing (Frontiers in Ecology and Evolution, 2021)
Lymphatic filariasis is a neglected parasitic disease that is a leading cause of long-term disability. Information obtained from genome sequencing of filarial worm can help us identify systems in the worm that are likely to be useful for novel drug design. Brugia (B.) malayi is still the only lymphatic-dwelling filarial parasite with a nearly complete, fully annotated, and published genome. However, most previous studies were based on the FR3 strain of B. malayi, which originally was isolated from a human patient, and was adapted to the rodent model, then maintained in laboratories for more than 60 years. It is uncertain whether genetic variation exists, thus, sequencing of clinical isolates of lymphatic dwelling filarial parasites is a high priority. Here, we report for the first time the complete mitochondrial genome of B. malayi microfilariae from clinical isolate. Complete mitochondrial (mt) genome of the microfilariae isolated from a blood sample taken from a Thai subject living in Narathiwat Province, which is an endemic area of brugian filariasis, was assembled with sequencing reads obtained by Illumina sequencing. Gene annotation, phylogenetic analysis and single nucleotide polymorphism (SNP) were deployed. A complete 13,658-bp mt genome of B. malayi microfilaria was obtained, and it shows 68x coverage. Based on gene annotation, the mt genome consists of 12 protein-coding, two rRNA, and 23 tRNA genes. Phylogenetic analysis using DNA sequences of mt genome or cytochrome c oxidase subunit I (COX1) revealed a close relationship among three lymphatic filariae (i.e., B. timori, zoonotic B. pahangi, and Wuchereria spp). The SNPs in the COX1 gene can differentiate microfilariae of B. malayi in human from those found in canine. Furthermore, the number, order and transcription, and direction of B. malayi microfilariae mitochondrial genes were the same as those found in the FR3 strain of B. malayi. The comparison on mitochondrial genome of B. malayi could have important implications on the development of a new intervention or vaccine to treat or prevent this disease in endemic areas/regions around the world.